Análise do tipo de substrato na fabricação de células solares bifaciais finas - Costa, Graziella Fernandes Nassau (2015)
The thin bifacial solar cells are a promising opportunity to reduce costs in manufacturing solar cells. These devices take advantage of solar radiation more efficiently by using the both sides of the solar cell to produce electricity. This study aimed to analyze the type of substrate, n and p, for the manufacture of thin bifacial solar cells with silicon substrate Czochralski (Cz-Si) with a thickness of 130 μm. The wafers, provided by the company Meyer Burger, were obtained by wire cutting process. The evaluation of the influence of texture processing time on the wafer, the diffusion/firing temperature optimization of metallic pastes deposited by screen printing and finally the comparison of the electrical parameters of solar cells with those from thin bifacial manufactured devices obtained by etching were performed. From a standard process of NT-Solar texture etch, two immersion times were tested, 50 min and 60 min, and the former showed the lowest weighted average reflectance and devices with higher short circuit density. The diffusion/firing of Ag and Al metallic pastes have been optimized considering the thermal processing temperature in the range between 850 ° C and 890 ° C. It was observed that the highest average efficiency were between 860 ° C and 870 ° C. The best performance were observed in the cells fabricated with phosphorous emitter in front and boron rear side, i.e., the structure n+np+ and n+pp+, and the efficiencies in front side was 12.8% and 13.6%, respectively and in the rear side 10.4 % and 9.0 %, respectively. By comparing these results with solar cells obtained by similar processes using chemical thinned wafers, the n+np+ structure had 1 % lower efficiency and the n+pp+ one presented similar efficiency values. Regarding the type of substrate, it can be concluded that the solar cells fabricated with the n-type substrate showed higher bifaciality, but the most efficient was manufactured with p-type silicon